A Feasibility study on coconut sugar - Apolinario, Napoleon Jr.; Santeco, Ryan Philip; Segovia, Cesar; Silva, Ronald (Diliman, Quezon City College of Engineering, 2000)
The coconut sugar is sugar derived from coconut sap.. This was conceptualized and realized by the Philippine Coconut Research and Development Foundation, Inc. (PCRDF) in 1993. It is very much similar to the raw or brown sugar since it is sweet and granular but has a mild coconut taste and aroma. It is produced by heating coconut sap to evaporate most of the sugar content. The product could be used as a substitute/alternative for brown sugar. It can be used mostly for beverages including coffee and juices, snacks, and many home cooked foods. It can also be used for native delicacies (bibingkas, rice cakes, puto, bananacue, turon, etc) and other food preparations. In general, it is cheaper and more nutritious than raw can sugar as it contains calcium, thiamin, niacin and a few other nutrients. Based on results of the market study, coconut sugar is feasible since there is a demand for the type of product and the demand exceeds the supply in the Philippines. With the population growth, the demand will be increasing while production continues to decline, leaving an increasing market share for the product every year. The coconut sugar is technically feasible. There are equipment available in the market to manufacture such product and there are land space and facilities available for the plantation of coconut trees. The choice of tree variety minimizes the traditionally labor intensive part of coconut sap collection of climbing tall trees. The system intended for coconut sugar somewhat deviates from the traditional practices of the other coconut industry players since 1) the workers are full time, 2) workers' salaries are fixed, 3) task schedules are strictly followed, and 4) worker shifts are implemented. The corporation form of business organization best suites the project. Since the capital required to start the project is large, the corporation would be able to finance it through its investors. The organizational structure determined is optimally effective for the company since all of the required duties and responsibilities of the personnel within the company are accounted for while keeping the minimum manpower level. And the hierarchy of the positions is also effective because proper authority is decentralized among the employees. The financial projections show that the project is feasible. Based on the cost-benefit analysis to society, the benefits greatly outweigh the disbenefits. It lay true to how the inventor envisioned the product to help the society - to give livelihood opportunities to many Filipinos, to help in the decrease in importations which lose the country much needed dollars, and to provide healthy competition to the once cane - based sugar industry. The Net Present Value for the benefits and disbenefits gave a positive value which means that society and the economy will derive net positive gains from the project making it socially profitable.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Philippine Coconut Research and Development Foundation, Inc. (PCRDF); Palm sugar; Coconut products--Philippines.; Participatory monitoring and evaluation (Project management)